Development policy and the training of foreigners - H. Pakleppa (Intereconomics, 1973)
Foreigners have always been able to study and follow practical courses in Germany long before the authorities responsible for cultural affairs abroad and those concerned with development policy began to take an active interest in these matters.
Keywords: 330; Germany